Thermoelectric Energy Harvesting For Powering LED Using Tealight - Tan Ngah Sie; Yong Zhe, Samuel Chow; Wai Ken, Leong; Kai Hong, Wong; Khoon Keat, Chow (Multidisciplinary Applied Research and Innovation, 2021)
In the 21st century, several topics are discussed about the impact of climate change, natural disasters and others that affect mother nature. Therefore, sustainable development is our main agenda in upcoming years to overcome the issue. Energy harvesting is a part of green technology that harvest waste energy around us in the form of heat energy, vibration energy, electromagnetic waves, etc. and convert it into easy-to-use electric energy. The fabricated device, called TEG Kit, harvest electricity by exposing a differences temperature across a thermoelectric generator (TEG) module. This is achieved by sandwiching the thermoelectric generator module with heatsink towards tealight candle at the optimum height of 7.5cm from base of the wooden block. The harvested voltage about 1.81V and connected series with DC-DC Booster have enough power to light the strip Light Emitting Diodes (LEDs). The significance of project has value-added in contribution of society to support rural communities without access of electricity for lighting.